2010
DOI: 10.2991/ijcis.2010.3.5.14
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Inference System for Robot Hand Optimal Grasp Preshaping

Abstract: This paper presents a novel Intelligent Inference System (IIS) for the determination of an optimum preshape for multifingered robot hand grasping, given object under a manipulation task. The IIS is formed as hybrid agent architecture, by the synthesis of object properties, manipulation task characteristics, grasp space partitioning, lowlevel kinematical analysis, evaluation of contact wrench patterns via fuzzy approximate reasoning and ANN structure for incremental learning. The IIS is implemented in software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The majority of the studies on dexterous manipulators reported in the literature have been focused on multi-finger multi-joint structures. C. V. Baysal et al 2010 [1] proposed an intelligent inference system for multi finger manipulators. Y. K. Cho et al 2011 [2] studied the control of a four finger manipulator.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the studies on dexterous manipulators reported in the literature have been focused on multi-finger multi-joint structures. C. V. Baysal et al 2010 [1] proposed an intelligent inference system for multi finger manipulators. Y. K. Cho et al 2011 [2] studied the control of a four finger manipulator.…”
Section: Introductionmentioning
confidence: 99%